L’« espace partagé » à l’encontre du « droit au logement » ? Lutte pour l’attribution légitime des logements sociaux en Irlande du Nord - Hadrien Herrault (L'Espace Politique)
This article explores a struggle over social housing allocation in Northern Ireland. Since the 1998 peace agreement, the Northern Ireland Executive has established “shared space” as a new policy legitimised under the term of “social mix”. It shapes this policy by defining a threshold which must be respected in the social housing allocation of “shared neighbourhoods” and which is based on an ethnic categorisation of applicants. In opposition, associations claim that this threshold could go against the “right to housing”, question social housing allocation based on housing “need” and generate possible discriminatory practices. By retracing this struggle, this article reviews the construction, based on alliances and oppositions, of “social mix” policies in Northern Ireland. It shows that the result of this struggle was not obvious. The Northern Ireland Executive had to develop symbolic strategies (by mobilising scientific reports, figures, stereotypes) and administrative strategies to conceal alternatives. Therefore, the article nuances the idea presenting the institutionalisation of “social mix” policies as the result of a uniform transnational circulation. Imposing “social mix” can be explained in Northern Ireland by structural changes linked to the neoliberalisation of social housing, but also by local changes linked to reconciliation policies and to adjustments in the face of local protests.